Associated Tinnitus Risk Factors in Patients with Type 2 Diabetes Mellitus - Puryani, Noorma Zuliana; Yenny, Yenny (Universitas Islam Bandung, 2024)
Tinnitus risk factors for type 2 diabetes mellitus (T2DM) are still under debate. Our study objective was to find tinnitus prevalence and principal risk factors in community-dwelling T2DM subjects. It was an analytical observational cross-sectional design study conducted from August to October 2023 at a public health center in West Jakarta. The consecutive non-random sampling method included 140 ambulatory T2DM study subjects. Tinnitus Screener and Tinnitus Handicap Inventory assessed tinnitus presence and severity. Age, sex, T2DM duration, fasting and 2-hour post-prandial blood glucose concentrations, lipid profile, blood pressure, and severity of hypertension were extracted from medical records. Data analysis was by chi-squared or Fisher exact tests, followed by multiple logistic regression analysis, with statistical significance set at p<0.05. The subjects' mean age was 54.71±5.33 years, and T2DM duration was 8.75±2.55 years. Tinnitus prevalence was 92 (65.17%), with 44 subjects (47.8%) having moderate tinnitus. Multivariable logistic regression findings: age (p=0.576), T2DM duration (p=0.116), total cholesterol (p=0.053), HDL-cholesterol (p=0.425), hypertension (p=0.046). Hypertension increased the risk of tinnitus by 2.289 times in T2DM subjects after adjusting for age, T2DM duration, and total and HDL cholesterol. Hypertension is the main tinnitus risk factor. The high tinnitus prevalence in our T2DM subjects requires regular screening for auditory function and control of blood pressure to minimize tinnitus risk in T2DM subjects.